PENGARUH PUNISHMENT DAN REWAARD TERHADAP KINERJA KARYAWAN SEBAGAI PERCEIVED ORGANIZATIONAL SUPPORT KERJA SEBAGAI VARIABEL INTERVENING - Hermawan; Febi Nur Utari; Dwi Rahmawati; Retno Purwani Setyaningrum (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2024)
This research aims to analyze the effect of punishment and reward on employee performance, with perceived organizational support (POS) as an intervening variable in the manufacturing company environment in the MM2100 area. The research method used was a questionnaire survey with a sample of 50 respondents as a data collection instrument. The respondents involved in this research were employees from various levels in manufacturing companies located in the MM2100 area. The results of data analysis using the regression method show that punishment has a significant negative effect on employee performance, while reward has a significant positive effect. Apart from that, work POS has also been proven to mediate the relationship between punishment, reward and employee performance. The results of these findings contribute to the understanding of the factors that influence employee performance in the manufacturing environment, especially in the context of providing punishment, rewards and perceived organizational support. This research provides practical implications for company management to optimize reward and punishment systems as a strategy to improve employee performance. In addition, this research also provides a theoretical basis for further research on the dynamics of the relationship between reward, punishment, work (POS), and employee performance in the context of the manufacturing industry